2020
DOI: 10.1155/2020/3640247
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Blood and Body Fluids among Health Care Workers in Gondar Town, Northwest Ethiopia: A Result from Cross-Sectional Study

Abstract: Background. Health care workers are at the greatest risk of developing blood-borne diseases through occupational exposure to blood and other contaminated body fluids. Occupational exposure to blood and body fluids (BBFs) continues to be the major public health problems and serious concern for the health care force in Ethiopia. Therefore, this study was aimed to determine the prevalence of exposure to blood and other body fluids and its associated risk factors among health care workers. Methods. The institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 44 publications
2
26
2
Order By: Relevance
“…This implies that a higher proportion of nurses are exposed to BBFs at the ED and ICU. The one-year exposure to BBFs is comparable with the study that was reported from India (68.64%), Tanzania (63%), Nigeria (68%), Gondar town (65.3%), and Mizan Tepi University (65.3%) (4,14,(19)(20)(21). However, the result is much higher than the study conducted in Turkey (13.7%), Iran (34.7%), Australia (48.1%), South Africa (21.9%), Kenia (22%), Tunisia (25.6%), Haramaya University (36.1%), Debre Berhan University (32.8%), and Arada sub-city health center, Addis Ababa (40%) (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This implies that a higher proportion of nurses are exposed to BBFs at the ED and ICU. The one-year exposure to BBFs is comparable with the study that was reported from India (68.64%), Tanzania (63%), Nigeria (68%), Gondar town (65.3%), and Mizan Tepi University (65.3%) (4,14,(19)(20)(21). However, the result is much higher than the study conducted in Turkey (13.7%), Iran (34.7%), Australia (48.1%), South Africa (21.9%), Kenia (22%), Tunisia (25.6%), Haramaya University (36.1%), Debre Berhan University (32.8%), and Arada sub-city health center, Addis Ababa (40%) (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionsupporting
confidence: 86%
“…The consequences of exposure to BBFs comprise the transmission of various types of pathogens like hepatitis B virus (HBV), hepatitis C virus (HCV), human immune de ciency virus (HIV), and other bloodborne pathogens that result in systemic and localized site infection (4,5). Furthermore, nerve damage from a needle stick may occur, as well as the possibility of the needle breaking off into the skin.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 10,233 healthcare workers were included in 18 studies, of which were conducted in 14 countries [ 16 , 25 – 41 ]: three articles [ 29 , 33 , 41 ] in Iran, two in Ethiopia [ 27 , 36 ], two in India [ 28 , 39 ], and one (5.55%) in other countries such as Nigeria [ 30 ], USA [ 25 ], China [ 31 ], Serbia [ 26 ], Saudi Arabia [ 32 ], Bangalore [ 34 ], Thailand [ 16 ], Australia [ 35 ], Bosnia and Herzegovina [ 37 ], Tanzania [ 38 ], and Switzerland [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the included articles, 6 articles [ 26 – 30 , 33 ] reported both prevalence of NSIs in career time and previous one year, while 6 [ 25 , 31 , 32 , 36 , 37 , 41 ] and 6 [ 16 , 34 , 35 , 38 – 40 ] of articles reported career time alone and previous one-year prevalence of NSIs alone, respectively. Most ( 5 (83.3%)) of the included articles [ 16 , 26 – 34 , 36 39 , 41 ] were conducted in the developing countries, while the rest of the studies [ 25 , 35 , 40 ] were in a developed country ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is much lower than the study carried out in Tanzania (82.5%) and Kenya (91.5%) [15,17].This considerable difference may be due to awareness regarding screening sources after exposure, fear of discrimination by colleagues, and less concern to infection transmitted via needle stick injury. [12,13,15,17]. This is due to the fact that lack of training increases the chances of exposure to sharp hazard.…”
Section: Discussionmentioning
confidence: 99%